A CASE OF REFRACTORY SUPRAVENTRICULAR TACHYCARDIA IN A NEWBORN. - dr pradnya wali (International Journal of Medical Research and Review, 2023)
Supraventricular Tachycardia (SVT) is the most common neonatal dysrhythmia with incidence being 1 in 100 for children of all ages and 1 in 250 for neonates. Origin of Supraventricular tachycardia is either above the bifurcation of the bundle of His or it has mechanisms dependent on the bundle of His. Newborns may present with irritability, poor feeding and tachypnea. The most important clinical signs of SVT is tachycardia sometimes associated with hypotension, heart failure, pallor, or decreased level of consciousness. Diagnosis is done with   heart rate continuously remaining  ≥ 220 beats per minute with a QRS < 0.08 seconds. Adenosine is the    first-line abortive therapy of choice. Intractable SVTs are treated with amiodarone, esmolol, and procainamide.  SVT with Circulatory collapse needs a synchronized DC cardioversion. Prognosis of SVT is generally excellent in the absence of structural heart disease.